Formulation and algorithms for route planning problem of plug-in hybrid electric vehicles - Murakami, Keisuke (Operational research, 2018)
Electric vehicles have recently received increasing attention because of their positive environmental and economic impacts; however, such vehicles are still not gaining widespread popularity for practical use given the inconvenience of limited battery capacity and long recharge times. To compensate for these drawbacks, plug-in hybrid electric vehicles (PHEVs) have been proposed, which can be recharged using standard household plug-in sockets unlike normal hybrid vehicles. Thus, PHEVs can run for long distances using widely available electrical power. Scheduling routes for the efficient use of electrical power is essential for PHEVs to succeed. Therefore, in this paper, we consider the PHEV routing and scheduling problem. We first formulate this problem as a mixed-integer programming (MIP) problem. Next, we propose three algorithms using a labeling method for large-scale problems; an exact algorithm and two heuristic algorithms. Our computational experiments show that the routes obtained using our algorithms are cost-efficient; further, our heuristic algorithms are much faster than the MIP formulation.